The hidden impact: social isolation and inflammation’s role in pancreatic cancer risk among those with diabetes - Lilu Ding; Jing Qian; Ruoqi Dai; Hui Zhang; Jingyou Miao; Jing Wang; Min Yu; Xiao Tan; Yingjun Li (BMC Cancer)
Abstract Background Pancreatic cancer poses a significant challenge in individuals with diabetes, prompting a reevaluation of established risk factors beyond conventional glycemic control measures. Objectives To explore the complex interplay of metabolic and psychosocial determinants in pancreatic cancer risk among individuals with diabetes, challenging prevailing perspectives and advocating for a comprehensive approach. Methods A total of 21,945 UK Biobank participants with baseline diabetes diagnosis were analyzed. Social isolation was assessed through a questionnaire capturing five factors: household size, social activities, friend/family visits, loneliness, and confiding in others. Incident pancreatic cancer was identified using ICD codes. Baseline characteristics, insulin use, and other relevant factors were analyzed. Hazard ratios and mediation analyses were conducted to determine the relationship between social isolation, inflammation, and pancreatic cancer risk. Results Individuals with high social isolation were more likely to be male, smokers, non-drinkers, and have shorter sleep duration. They also had an increased risk of pancreatic cancer (HR = 2.65, 95% CI = 1.12–6.24) compared to those with low social isolation. Mediation analyses highlighted inflammation as a crucial mediator, with the proportion mediated by inflammation being 19.44% for insulin use, 10.34% for smoking, and 8.33% for social isolation. Conclusions Our findings highlight the importance of psychosocial factors in pancreatic cancer risk and underscore the need for further research to elucidate the underlying mechanisms.